ENSURING THE INVESTMENT ATTRACTIVENESS OF PILGRIMAGE TOURISM PROJECTS - Firuza Tuqbayeva (American Journals, 2024)
Pilgrimage tourism, a sector that holds significant cultural and economic potential, has gained attention as a key area for development in many countries. This article discusses the challenges and strategies involved in ensuring the investment attractiveness of pilgrimage tourism projects. The analysis focuses on identifying factors that can boost investment, the role of infrastructure, government support, and the specific characteristics of pilgrimage tourism that differentiate it from other types of tourism.
Keywords: Pilgrimage tourism, investment attractiveness, infrastructure, tourism development, government support, cultural tourism.